1997
DOI: 10.1007/bf02505319
|View full text |Cite
|
Sign up to set email alerts
|

Serum CA 125 levels and survival in advanced ovarian cancer

Abstract: We made a retrospective analysis of 85 patients with elevated serum CA 125 after surgery for ovarian cancer. Absolute CA 125 serum levels were a poor guide to prognosis. However, the ratio between the serum CA 125 after the first, second, or third course of treatment and the postoperative value was an excellent guide to prognosis. These were also independent and stable in the Cox Regression analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
1
5
0
2
Order By: Relevance
“…Rustin et al [10] reported that CA125 can give prognostic information based on serial CA125 levels to measure the response of ovarian carcinoma in patients receiving first-line chemotherapy. In the present study, we demonstrated that absolute CA125 serum levels were a poor guide to prognosis, in accordance with other studies [11,12]. In addition, STN has been shown to be independently associated with prognosis and a strong prediction of survival [13].…”
Section: Discussionsupporting
confidence: 92%
“…Rustin et al [10] reported that CA125 can give prognostic information based on serial CA125 levels to measure the response of ovarian carcinoma in patients receiving first-line chemotherapy. In the present study, we demonstrated that absolute CA125 serum levels were a poor guide to prognosis, in accordance with other studies [11,12]. In addition, STN has been shown to be independently associated with prognosis and a strong prediction of survival [13].…”
Section: Discussionsupporting
confidence: 92%
“…3 Several authors have explored the clinical significance of serum CA-125 changes during the early postoperative period, but there is still no agreement regarding the prognostic value of post-operative CA-125. [4][5][6] The clinical significance of serum CA-125 decline immediately after primary cytoreductive surgery is uncertain. Furthermore, the relationship between postoperative declines of serum CA-125 and survival has not been clearly defined yet.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the class membership is certain, the parameter estimation does not lead to loss of efficiency ([31]). Although we only used biomarker trajectory data in the first stage to estimate the latent class membership, the misclassification rate should be low since the trajectory describes biomarker behavior and significantly correlated with survival ([48], [49], [50], [51], [52], [53]) and the biomarker trajectory pattern has been viewed as a latent class, and moreover we used MI to account for the uncertainty of latent class membership which helps minimize loss of efficiency. Specifically in our example the estimated misclassification rate, presented in Section 4.2, is low.…”
Section: Discussionmentioning
confidence: 99%